2015
DOI: 10.1177/1087054715613436
|View full text |Cite
|
Sign up to set email alerts
|

Internet Activities During Leisure: A Comparison Between Adolescents With ADHD and Adolescents From the General Population

Abstract: Adolescents' leisure activities are increasingly focusing on Internet activities and today, these co-exist with traditional leisure activities such as sport and meeting friends. Objective: To investigate leisure activities, particularly Internet activities, among boys and girls with attention deficit/hyperactivity disorder (ADHD), and compare these to boys and girls from the general population. The objective was also to explore how traditional leisure activities and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(80 reference statements)
2
10
0
1
Order By: Relevance
“…As expected, total media time increased on weekends in both groups; however, patients’ screen time exceeded remarkable 5 hr per day, suggesting that affected children spend a great amount of their spare time with electronic devices. In support of our findings, there is evidence that girls and boys with ADHD are less frequently involved in traditional leisure activities, such as meeting with friends, sports, and acting/dancing, and express less enjoyment in extracurricular activities than typically developed children do (Bolic Baric et al, 2018; Shimoni, Engel-Yeger, & Tirosh, 2010). Bolic Baric et al (2018) found that patients with ADHD prefer Internet-based channels to engage in social interactions with their peers, possibly to avoid confrontation with their behavioral difficulties and ascertaining feelings of competence (Shimoni et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As expected, total media time increased on weekends in both groups; however, patients’ screen time exceeded remarkable 5 hr per day, suggesting that affected children spend a great amount of their spare time with electronic devices. In support of our findings, there is evidence that girls and boys with ADHD are less frequently involved in traditional leisure activities, such as meeting with friends, sports, and acting/dancing, and express less enjoyment in extracurricular activities than typically developed children do (Bolic Baric et al, 2018; Shimoni, Engel-Yeger, & Tirosh, 2010). Bolic Baric et al (2018) found that patients with ADHD prefer Internet-based channels to engage in social interactions with their peers, possibly to avoid confrontation with their behavioral difficulties and ascertaining feelings of competence (Shimoni et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Although there is still no comprehensive information about media use in ADHD, the scant studies undertaken so far indicate that individuals with ADHD are more attracted to electronic media and engage in more screen time than typically developed peers (Acevedo-Polakovich, Lorch, & Milich, 2007; Bolic Baric, Hellberg, Kjellberg, & Hemmingsson, 2018). Examining the association of the availability of a bedroom TV with total screen time among 6- to 17-year-olds with ADHD revealed that they spend 150 min per weekday watching TV, watching videos, or playing video games (Lo, Waring, Pagoto, & Lemon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The current study provides new insight into several leisure activities, including a variety of specific Internet activities, particularly online and video games that characterize leisure among boys and girls with ADHD, compared with adolescents from the general population [13]. Leisure activities can provide adolescents with an opportunity to develop skills and competencies, increased physical and psychological development, and a sense of belonging.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd) and Attenmentioning
confidence: 91%
“…Leisure activities can provide adolescents with an opportunity to develop skills and competencies, increased physical and psychological development, and a sense of belonging. Conclusively internet activities, especially social communities and downloading music, might provide adolescents with ADHD with accessible means of social interaction where individuals can interact with each other in physical and virtual spaces [13].…”
Section: Attention Deficit Hyperactivity Disorder (Adhd) and Attenmentioning
confidence: 99%
See 1 more Smart Citation